2015
DOI: 10.1002/cyto.a.22726
|View full text |Cite
|
Sign up to set email alerts
|

Kinin‐B1 and B2 receptor activity in proliferation and neural phenotype determination of mouse embryonic stem cells

Abstract: The kinins bradykinin and des-arg 9 -bradykinin cleaved from kininogen precursors by kallikreins exert their biological actions by stimulating kinin-B2 and B1 receptors, respectively. In vitro models of neural differentiation such as P19 embryonal carcinoma cells and neural progenitor cells have suggested the involvement of B2 receptors in neural differentiation and phenotype determination; however, the involvement of B1 receptors in these processes has not been established. Here, we show that B1 and B2 recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have shown that bradykinin induces an elevation in the concentration of intracellular free Ca 2+ ([Ca 2+ ] i ) by activating B2BkR in four models of neural differentiation (Appell and Barefoot, 1989;Martins et al, 2008Martins et al, , 2005Nascimento et al, 2015;Trujillo et al, 2012). Thus, we aimed to find the intracellular signaling pathways that mediate the bradykinin-induced [Ca 2+ ] i increase.…”
Section: Signaling Pathways Activated By Bradykinin In Npcsmentioning
confidence: 99%
“…Previous studies have shown that bradykinin induces an elevation in the concentration of intracellular free Ca 2+ ([Ca 2+ ] i ) by activating B2BkR in four models of neural differentiation (Appell and Barefoot, 1989;Martins et al, 2008Martins et al, , 2005Nascimento et al, 2015;Trujillo et al, 2012). Thus, we aimed to find the intracellular signaling pathways that mediate the bradykinin-induced [Ca 2+ ] i increase.…”
Section: Signaling Pathways Activated By Bradykinin In Npcsmentioning
confidence: 99%
“…Cells were passed through a 40 mm cell strainer, centrifuged, then fixed for 20 min in 4% paraformaldehyde (PFA) at room temperature (RT), washed with PBS supplemented with 2% FBS, and incubated for 30 min at RT with mouse anti-B2R (1:100; BD Biosciences) and rabbit anti-B1R (1:100; Abcam) primary antibodies in PBS plus 0.1% Triton X-100 and 2% FBS. After washing with 900 ml of PBS plus 2% FBS, the secondary anti-mouse antibodies conjugated with Alexa Fluor (AF) 647 and anti-rabbit conjugated antibodies with AF 488 (both at 1:500 dilutions; Life Technologies) were added and incubated for 30 min at RT (18,19). After a final washing step, the cells were re-suspended in 400 ml of PBS and analyzed on a flow cytometer (BD Accuri C6, BD Biosciences).…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…More recently, studies have demonstrated the role of BK in neurite outgrowth, proliferation inhibition of stem cells and their differentiation into neurons (Martins et al, 2005;Trujillo et al, 2009;Trujillo et al, 2012;Nascimento et al, 2015;Pillat et al, 2015). At a molecular level, BK and B2BKR are also involved in ERK activation, acting via tyrosine kinases Pyk2 and Src (Ca 2+ -dependent pathway), and via EGF and PKC pathway, respectively (Dikic et al, 1996;Adomeit et al, 1999).…”
Section: Bradykinin and Neurogenesismentioning
confidence: 99%